2011
DOI: 10.1007/s12070-011-0297-4
|View full text |Cite
|
Sign up to set email alerts
|

Value of Fine-Needle Aspiration Cytology in the Evaluation of Parotid Tumors

Abstract: Fine needle aspiration cytology (FNAC) is commonly used in the study of parotid masses; however controversy exists regarding its diagnostic accuracy. The objective of this study was to evaluate the effectiveness of FNAC as a preoperative diagnostic tool of parotid tumors. Sixty-five patients had satisfactory preoperative FNAC and underwent subsequent surgery to the parotid between March 2002 and July 2009 at our institution. The results of the FNAC were compared to the permanent histopathological diagnosis. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“… Diagnosing lymphoma is very difficult , among pathologist experiences. [13][14][15][16][17][18][19][20][21] Good collaboration between the otorhinolaryngologist and the pathologist provides the best results. However, in the context of a non-diagnostic FNAB, high suspicion for parotid malignancy may be warranted for otorhinolaryngologist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Diagnosing lymphoma is very difficult , among pathologist experiences. [13][14][15][16][17][18][19][20][21] Good collaboration between the otorhinolaryngologist and the pathologist provides the best results. However, in the context of a non-diagnostic FNAB, high suspicion for parotid malignancy may be warranted for otorhinolaryngologist.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the context of a non-diagnostic FNAB, high suspicion for parotid malignancy may be warranted for otorhinolaryngologist. [19][20][21][22] FNAB under ultrasound guidance has higher sensitivity more than blind FNAB. Bajaj et al and Pratap et al reported that the sensitivity of FNAB was increased by 20% from to 65% to 85%, respectively, with using ultrasound guidance.…”
Section: Discussionmentioning
confidence: 99%
“…27 The most important reasons leading to misdiagnosis and false negatives are lack of necessary expertise, presence of atypical cells in both benign and malignant lesions, association of chronic sialadenitis with several types of malignancy, and difficulty in diagnosing lymphoma. 28 Diagnostic dilemma has been reported in cases where mucoepidermoid carcinoma and/or Warthin's tumor present as cystic swellings, aspiration reveals inflammation instead of pleomorphic adenoma, adenoid cystic carcinoma is misinterpreted as pleomorphic adenoma or basal cell adenoma on aspiration cytology, and Warthin's tumor is cytodiagnosed as squamous cell carcinoma. 25 There are various lesions in the oral cavity, floor of mouth, tongue, palate, tonsils, and posterior pharyngeal wall that can be assessed by needle under visual control; however, little data have been published regarding usefulness of FNAC in the diagnosis of intraoral lesions.…”
Section: Discussionmentioning
confidence: 99%
“…This is reinforced with the PPV of a ‘neoplastic’ FNAC result being 100% compared with the PPV for a benign FNAC result being only 86%. Previous studies have also reported a low sensitivity for malignancy but high specificity …”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have also reported a low sensitivity for malignancy but high specificity. 6,7,11,12 There is limited literature comparing the efficacy of FNAC with imaging studies to identify parotid neoplasms and most published data focuses on the ability of specific imaging modalities to identify malignant parotid tumours. In comparing the results of this study to recent literature, FNAC showed lower sensitivity to computed tomography (CT) in identifying malignant lesions, 75 versus 100%, but greater specificity, 97.5 versus 42%.…”
Section: Discussionmentioning
confidence: 99%